Research of antioxidant properties of theophyllinyl-7-acetic acid derivatives - Aleksandrova, Katherine; Belenichev, I. F.; Shkoda, Alexander; Levich, Sergey; Yurchenko, Darja; Buchtiyarova, Nina; Александрова, Катерина Вячеславівна; Бєленічев, Ігор Федорович; Шкода, Олександр Станіславович; Левіч, Сергій Вадимович; Юрченко, Дар'я Миколаївна; Бухтіярова, Ніна Вікторівна (Nigeria: Department of Environmental Health Sciences, Faculty of Public Health, College of Medicine, University of Ibadan, 2014)
Objective: Accumulation of reactive oxygen species and nitric oxide (NO) derivatives in the cell exerts damaging effects on its constituents, such as carbohydrates, proteins, lipids, and nucleic acids. These processes has been determined to play a significant role as a nonspecific pathogenetic mechanism in development of multiple disease states, such as atherosclerosis, ischemic stroke, diabetes, etc. The search for antioxidant compounds capable of interrupting the pathological biochemical processes at various steps of oxidative and nitrosative stress development, and thus exerting prophylactic and therapeutic effects, is a priority for medical and pharmaceutical sciences. In this article we investigated the effects of newly synthesized esters, hydrazides and hydrazones of theophyllinyl-7-acetic acid on late markers of oxidative and nitrosative stresses. Methods: Investigation of antioxidant properties of xanthine derivatives was carried out using following in vitro methods: inhibition of the NO radical, inhibition of oxidative modification of proteins, and initiation of lipid peroxidation Results: Hydrazides and benzylidene-hydrazides of theophyllinyl-7-acetic acid showed more pronounced antioxidant properties than esters. The most active compounds among tested theophyllinyl-7-acetic acid derivatives were hydrazide and (1-phenylethyliden)hydrazide of (8-N-benzylaminotheophyllinyl-7)acetic acid. Conclusions: In vitro studies of 23 derivatives of theophyllinyl-7-acetic acid have been shown that almost all compounds exhibit antioxidant properties. The obtained results also helped us to establish some patterns of structure-activity relationship.
Keywords: esters; hydrazides; theophyllinyl-7-acetic acid; spectroscopy